Regular training has a greater effect on aerobic capacity, fasting blood glucose and blood lipids in obese adolescent males compared to irregular training - Hosein Karami; Vahid Valipour Dehnou; Afshin Nazari; Daniel Gahreman (Elsevier, 2021)
Background/Objective: It is not clear whether the regularity of training affects the outcomes of aerobic exercise. This study aimed to compare the effects of regular with irregular training on aerobic fitness, blood markers, and anthropometric characteristics of obese adolescent males. Methods: Twenty three male students between 16 and 17 years old were randomly assigned into regular exercise (RE) group and performed exercises on specific time and days each week, or irregular exercise (IE) group and performed exercise on randomly selected days each week. The intervention programs consisted of self-paced progressive running program (20 min in week one and 44 min in week 8), three times per week for eight weeks. Anthropometric characteristics, blood lipids, fasting blood glucose, and aerobic capacity were assessed before and after the intervention using a two-way ANOVA. Results: There was a significant interaction of time and condition on total cholesterol (TC) F (1, 21) = 5.427, p = 0.030, ηP2 = 0.205, and high-density lipoprotein to low-density lipoprotein ratio (HDL)/(LDL) F (1, 21) = 5.951, p = 0.024, ηP2 = 0.221), with a greater reduction observed in RE group. LDL decreased only in RE group demonstrating a significant effect of time F (1, 21) = 4.897, p = 0.038, ηP2 = 0.189. Body mass, body mass index (BMI), and waist circumference decreased, and VO2peak increased in both groups with no significant difference between groups. There was no significant effect of time or condition on waist to hip ratio (WHR), fasting blood glucose (FBG), triglycerides (TG), HDL, TC/HDL, or TG/HDL (p > 0.05). Conclusion: Although both RE and IE improved VO2peak and some anthropometric measures, changes in TC, LDL, and HDL/LDL were more predominant in response to RE. Therefore, to achieve greater adaptations to aerobic exercise, overweight and obese adolescents should perform exercise regularly.